Unions power, collective bargaining and optimal monetary policy - Ester Faia; Lorenza Rossi (Kiel Institute for the World Economy (IfW), 2008)
We study the design of optimal monetary policy (Ramsey policies) in a model with sticky prices and unionized labour markets. Collective wage bargaining and unions monopoly power tend to dampen wage fluctuations and to amplify employment fluctuations relatively to a DNK model with walrasian labour markets. The optimal monetary policy must trade-off counteracting forces. On the one side deviations from zero inflation allow the policy maker to smooth inefficient employment fluctuations. On other side, the presence of wage mark-ups and wage stickiness produce inflationary pressures that require aggressive inflation targeting. Overall we find that the Ramsey planner deviates from full price stability and that an optimal rule targets inflation the real economic activity alongside inflation.
Keywords: E0; E4; E5; E6; 330; Optimal monetary policy; labour market unionization; threat points; Geldpolitik; Inflation Targeting; Tarifpolitik; Gewerkschaftlicher Organisationsgrad; Optimale Besteuerung; Dynamisches Gleichgewicht; Europäische Wirtschafts- und Währungsunion; Theorie